Insuficiencia de convergencia en paciente femenino de 8 años de edad. - Mariscal Valvera, Ángel Samuel (2023)
In the present clinical case, it is an 8-year-old female patient who has been diagnosed with convergence insufficiency. Convergence insufficiency (CI) was defined as one of the most frequent binocular vision problems in daily optometric practice. It has been determined as the inability to obtain or maintain an ideal convergence without effort. CI is the most common binocular vision disorder, it is characterized by muscle coordination problems, where the eyes cannot work together when fixing sight on a certain point, the objective of this clinical case is to demonstrate the effects of insufficient vision. convergence in the 8-year-old female patient. The research focuses on improving the visual quality of the patient, eliminating the discomfort caused by said dysfunction. In the present study, the following optometric tests were performed, such as visual acuity (VA), RX, fundus, near point of convergence (PPC), ocular motility, cover test, among others. Among all the results that were obtained in the study through the diagnostic tests of this clinical case, it was an insufficiency of convergence, the treatment applied will be visual therapy with a training plan for 12 weeks, which is recommended a control every 3 months with the trusted optometrist.